Wild Cards. Imagination als Katastrophenprävention - Weber, Jutta (Zeitschrift für Kulturwissenschaft, Sonderausgabe zum Thema ‚Vorstellungskraft‘ (Hg.: Siegfried Mattl, Christian Schulte))

Opacity versus Computational Reflection. Modelling Human-Robot Interaction in Personal Service Robotics - Weber, Jutta (Science, Technology and Innovation Studies. Vol. 10, No.1, January 2014)

Donna Haraway. Technoscience, New World Order und Trickster-Geschichten für lebbare Welten - Weber, Jutta (Schlüsselwerke der Wissenschafts- und Technikforschung/Science & Technology Studies)

Opacity versus Computational Reflection. Modelling Human-Robot Interaction in Personal Service Robotics - Weber, Jutta (Science, Technology and Innovation Studies, Vol. 10, No. 1)

Mechatronischer Entwurf und Erprobung einer regelbaren Federung für ein leichtes geländegängiges Kettenfahrzeug - Illg, Igor

Entwurf mechatronischer Fahrzeugfederungen am Beispiel eines geländegängigen Nutzfahrzeugs - Wielenberg, Andreas

Optimale Steuerung und Mehrzieloptimierung von dynamischen Systemen untersucht am Beispiel des Mehrfachpendels - Timmermann, Julia
In dieser Arbeit wird gezeigt, wie optimale Trajektorien für ein unteraktuiertes mechanisches System - das Doppel- bzw. Dreifachpendel auf einem Wagen - mittels optimaler Steuerung bestimmt werden können. Dabei werden neuartige mathematische Methoden verwendet und deren Vorteile in der Anwendung aufgezeigt. Es werden sowohl die theoretischen Ergebnisse analysiert als auch die praktische Umsetzung in Simulationen und am Prüfstand untersucht. Das Manöver, welches hier hauptsächlich betrachtet wird, ist der Aufschwung des Pendels aus der stabilen unteren Ruhelage in die instabile obere Ruhelage. Dabei werden mit Hilfe von Methoden der Mehrzieloptimierung viele Varianten von Lösungen berechnet, die die zwei gegenläufigen Zielgrößen Dauer des Manövers und Steueraufwand unterschiedlich stark berücksichtigen. So ist es möglich eine komplexe Bibliothek von optimalen Lösungen zu erhalten und diese weitergehend bezüglich des Gesamtsystemverhaltens zu analysieren. Ein weiterer Ansatz ist die Entwicklung von Strategien für eine optimale Steuerung auf Mannigfaltigkeiten, die besondere dynamische Strukturen des Pendelsystems für einen optimalen Aufschwung nutzen. Auf der stabilen Mannigfaltigkeit kann sich das dynamische System kostenlos in die Ruhelage bewegen. Dies ist somit ein besonderer physikalisch motivierter Ansatz, um optimale Manöver zu finden.

Hardness of approximation for quantum problems - Gharibian, Sevag; Kempe, Julia (Quantum Information & Computation)
The polynomial hierarchy plays a central role in classical complexity theory. Here, we define a quantum generalization of the polynomial hierarchy, and initiate its study. We show that not only are there natural complete problems for the second level of this quantum hierarchy, but that these problems are in fact hard to approximate. Using the same techniques, we also obtain hardness of approximation for the class QCMA. Our approach is based on the use of dispersers, and is inspired by the classical results of Umans regarding hardness of approximation for the second level of the classical polynomial hierarchy [Umans, FOCS 1999]. The problems for which we prove hardness of approximation for include, among others, a quantum version of the Succinct Set Cover problem, and a variant of the local Hamiltonian problem with hybrid classical-quantum ground states.
Keywords: Hardness of approximation; polynomial time hierarchy; succinct set cover; quantum complexity

Gate-efficient discrete simulations of continuous-time quantum query algorithms - W. Berry, Dominic; Cleve, Richard; Gharibian, Sevag (Quantum Information & Computation)
We show how to efficiently simulate continuous-time quantum query algorithms that run in time T in a manner that preserves the query complexity (within a polylogarithmic factor) while also incurring a small overhead cost in the total number of gates between queries. By small overhead, we mean T within a factor that is polylogarithmic in terms of T and a cost measure that reflects the cost of computing the driving Hamiltonian. This permits any continuous-time quantum algorithm based on an efficiently computable driving Hamiltonian to be converted into a gate-efficient algorithm with similar running time.

Special Issue: Philosophers of the World Unite! Theorising Digital Labour and Virtual Work - Definitions, Dimensions and Forms - Fuchs, Christian; Sandoval, Marisol; Prodnik, Jernej A.; Sevignani, Sebastian; Allmer, Thomas (tripleC: Communication, Capitalism & Critique)